On some types of slight homogeneity - Samer Al Ghour; Nahed Al Khatib (International Journal of Electrical and Computer Engineering (IJECE), 2020)
As a generalization of the concept SLH space, we introduce the concept of slightly strongly locally homogeneous (SSLH) spaces. Also, we introduce the concepts of slightly dense set as well as slightly separable space, and use them to introduce two new types of slightly countable dense homogeneous spaces. Several results, relationships, examples and counter-examples concerning these concepts are obtained.